A successful desensitization protocol for horse‐derived antithymocyte globulin in severe aplastic anemia. Issue 2 (March 2015) - Demir, Esen; Cigerci Günaydın, Nurşen; Karadaş, Nihal; Gülen, Figen; Tanac, Remziye; Yılmaz, Deniz
Abstract: Background: Horse antithymocyte globulin (h‐ATG) (ATGAM ® ) is the first choice of treatment in very severe patients with aplastic anemia who do not have any HLA matched sibling donor. h‐ATG is a heterologous serum that may cause anaphylaxis. Alternative treatment strategies must be planned in case of hypersensitivity. Desensitization must be considered in patients without an alternative treatment of choice. We aimed to present the h‐ATG desensitization protocol and consider its effectiveness in patients with aplastic anemia who are hypersensitized with h‐ATG and do not have an alternative treatment of choice. Methods: Skin prick tests were performed with non‐diluted solution in eight very severe patients with aplastic anemia who are followed up in Ege University Children's Hospital. Although skin prick test was found negative in these eight patients, different dilution h‐ATG intradermal tests were performed and found positive in all patients. h‐ATG desensitization program was started to these hypersensitized patients. Results: Desensitization program was started to six male and two female very severe patients with aplastic anemia whose ages were between seven and 19 yr (median: 12.9 yr). All of the patients completed the desensitization program. While local reaction was seen in two patients, systemic reaction was seen in one patient and late reaction was seen in one patient during and after desensitization program. Conclusion: A successful desensitization program with h‐ATG in children with aplastic anemia is presented. Even though there is not an exposure before to such high allergy potential heterologous serum, skin tests should be performed and desensitization must be started to patients who are hypersensitized to h‐ATG. As the expected effectiveness of the treatment is so much, the desensitization protocol can be carried out safely and effectively with trained stuff although allergic reactions can be seen.